2014
DOI: 10.1016/j.orcp.2012.08.193
|View full text |Cite
|
Sign up to set email alerts
|

Parental feeding patterns and child weight status for Latino preschoolers

Abstract: Objective To examine the relationships between parental patterns regarding child feeding and child Body Mass Index (BMI) percentile in Latino parent-preschooler dyads participating in a clinical trial. Methods This secondary analysis examined data collected during a randomized clinical trial of a culturally tailored healthy lifestyle intervention focused on childhood obesity prevention, Salud Con La Familia. We analyzed 77 Latino parent-child dyads who completed baseline and 3-month follow-up data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
(40 reference statements)
3
22
1
10
Order By: Relevance
“…When the children were evaluated by birth weight, it was found that 83.7% of the children were born with a normal birth weight (2500-4000 g), 8.7% were born with a low birth weight (<2 500 g) and 7,7% were born with a high birth weight (>4 000 g). According to the BMI standard deviation score, 79.7% of the children had a normal body weight, 12.3% were obese and 8% had a low body weight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the children were evaluated by birth weight, it was found that 83.7% of the children were born with a normal birth weight (2500-4000 g), 8.7% were born with a low birth weight (<2 500 g) and 7,7% were born with a high birth weight (>4 000 g). According to the BMI standard deviation score, 79.7% of the children had a normal body weight, 12.3% were obese and 8% had a low body weight.…”
Section: Resultsmentioning
confidence: 99%
“…Especially in the preschool period, parents are responsible of choosing foods for their children and they try to develop adequate and balanced nutritional behavior by using different feeding methods (2). Parental feeding style is affected by many factors including the perception of the child's weight by the parents (3), the child's weight (2)(3)(4)(5)(6), gender (7), the weight of the parents (8,9) and the economical and education status of the parents (2,10).…”
Section: Introductionmentioning
confidence: 99%
“…Wilayah Kalijudan menepati posisi paling tinggi dengan status gizi sangat kurus 2 balita dan kurus 97 balita. Menurut Karp et al, (2012) menjelaskan bahwa pola makan dan perilaku orang tua seperti memonitor asupan nutrisi, membatasi jumlah makanan, respon terhadap pola makan, dan memperhatikan status gizi anak memberikan dampak yang berarti bagi status gizi anak.…”
Section: Pendahuluanunclassified
“…The feeding relationship is complex between the parent and child; effective feeding provides the groundwork for growth patterns and healthy eating behaviors. 28,106 Parents are role model for food preferences; hence, it stands to reason that children's food preferences are positively correlated to their parent's food preferences. 107 Preschoolers, whose mothers skipped breakfast and did not eat fruits and vegetables, had the highest incidence of poor nutritional status.…”
Section: Preschoolers (2-5 Years)mentioning
confidence: 99%
“…111 Many studies have shown that to implement a lifestyle such as eating a healthy diet, the whole family needs to be involved for food consumption patterns to shift. 106 Thirty-year trends in preschoolers' food choices correspond with the national food supply and are influenced by taste, television, and cultural norms. 111 However, on any given day, preschoolers did not eat a balanced diet; 90% drank milk and ate some type of protein, but only 69.8% ate any vegetables (~60% of the vegetables consumed were potatoes) and 75.6% ate fruit or fruit juice (fruit juice was the predominate fruit).…”
Section: Preschoolers (2-5 Years)mentioning
confidence: 99%